Enhancing Logistics Efficiency: A Comprehensive Study of Royal Solidex company - Ali Khamis Ali Ambu Saidi; Dr. Naim Ayadi (IJRDO - Journal of Business Management, 2025)
The logistics sector is a cornerstone of global supply chains, facilitating the timely and efficient movement of goods and services. Despite its critical role, the industry faces persistent challenges, including inefficiencies in shipment tracking, delivery delays, communication gaps, and reliance on outdated technological infrastructure. This research paper investigates these challenges and evaluates advanced solutions such as modern tracking technologies, predictive analytics, and automation in logistics operations. Adopting a mixed-methods approach, the study combines qualitative and quantitative analysis to examine industry trends and propose actionable interventions. The findings highlight the pivotal role of digital transformation in enhancing operational efficiency, minimizing delays, and improving customer satisfaction, ultimately driving the competitiveness of the logistics sector.